Accelerating units for commercial resonator LINACs model UELR-10-10S designed for radiation sterilization development and results of testing - Alexeev, V.A.; Baranovsky, A.E.; Belousov, A.V.; Davydov, V.N.; Demsky, M.I.; Denisov, K.A.; Fialkovsky, A.M.; Fomin, L.P.; Gavrish, Yu.N.; Kochin, S.N.; Larionovsky, V.A.; Maslov, K.N.; et al. (Вопросы атомной науки и техники, 2006)
Some specific design features of the accelerating units for LINACs model UELR-10-10S designed for radiation sterilization and the electron beam characteristics obtained experimentally are considered. Описываются некоторые особенности конструкции ускорителей модели УЭЛР-10-10С, приводятся и обсуждаются характеристики электронного пучка, полученные экспериментально. Описуються деякі особливості конструкції прискорювачів моделі УЕЛР-10-10С, приводяться і обговорюються характеристики електронного пучка, отримані експериментально.